Comprehensive analysis of differences in N6-methyladenosine RNA methylomes in Helicobacter pylori infection - Li, Huan; Lin, Jiahui; Cheng, Sha; Chi, Jingshu; Luo, Ju; Tang, Yu; Zhao, Wenfang; Shu, Yufeng; Liu, Xiaoming; Xu, Canxia (Frontiers in Cell and Developmental Biology, 2023)
Background: Helicobacter pylori (H.pylori) infection is an essential factor in the development of human gastric diseases, but its pathogenic mechanism is still unclear. N6-methyladenosine(m6A) modification is the most abundant reversible epitranscriptomic modification in mammalian RNA and plays a vital role in many biological processes. However, it is unclear whether H. pylori infection impacts m6A RNA methylation in stomach. In this study, we measured the global level of m6A RNA methylation in vitro and in vivo experiment. Methods: The total quantity of m6A was quantified in gastric tissues of clinical patients and C57 mice with H. pylori infection, as well as acute infection model (H. pylori and GES-1 cells were cocultured for 48h at a multiplicity of infection MOI from of 10:1 to 50:1). Furthermore, we performed m6A methylation sequencing and RNA-sequencing on the cell model and RNA-sequencing on animal model. Results: Quantitative detection of RNA methylation showed that H. pylori infection group had higher m6A modification level. M6A methylation sequencing identified 2107 significantly changed m6A methylation peaks, including 1565 up-regulated peaks and 542 down-regulated peaks. A total of 2487 mRNA was up-regulated and 1029 mRNA was down-regulated. According to the comprehensive analysis of MeRIP-seq and RNA-seq, we identified 200 hypermethylation and up-regulation, 129 hypermethylation but down-regulation, 19 hypomethylation and down-regulation and 106 hypomethylation but up-regulation genes. The GO and KEGG pathway analysis of these differentially methylated and regulated genes revealed a wide range of biological functions. Moreover, combining with mice RNA-seq results, qRT- PCR showed that m6A regulators, METTL3, WTAP, FTO and ALKBH5, has significant difference; Two key genes, PTPN14 and ADAMTS1, had significant difference by qRT- PCR. Conclusion: These findings provide a basis for further investigation of the role of m6A methylation modification in H. pylori-associated gastritis.